The Impact of Information Systems on Business Processes in the Financial Industry: A Case Study of SIC Life Saving and Loans Company Limited - Zormelo, C.K. (University Of Ghana, 2020)
In most organisations, the influence of information management is a significant challenge and a source of problems. As such causes, numerous economic difficulties, technological challenges and problems in changing organizational structures are frequently listed. This study seeks to assess the impact of an information system (IS) on business performance and the benefits derived from information systems. The study evaluated the impact of IS System Quality, IS Application Quality and Application Quality on IS Usage at financial institutions as well as the overall net benefits. Data for the study was collected from Sic Life Savings and Loans (SLSL). The study had a total sample of 195 respondents. Partial Least Square-Structural Equation Modeling (PLS-SEM) technique for data processing has been introduced. The findings of the study show positive relationships between IS System Quality, IS information Quality, IS Application Quality and IS Usage at the financial institution. Only the relationship between IS System and Is usage was not statistically significant. The relationship between IS Usage and Net benefit derived from information system was significant and positively correlated. The results from the study show the positive impact of information system on organizations that implement IS. The study provides relevant and helpful conclusions and recommendations for practice, policymaking and future research. For practice, the study has provided information on the use and benefit IS system. This study can serve as a guide for the development, implementation and evaluation of IS system and applications. This study highlights some qualities that can help IS system developers and guide users to choose the best System that will give the best benefit. For policy, management of organizations, unions and government can follow the result of this study to implement policies to regulate the use of IS systems and increase its patronage. The impact of the IS system on organizations has been proven over the years, and this study provides support for Ghanaian based industries to implement the IS.
MBA. Management Information Systems
Keywords: Information Systems; Financial Industry; SIC